2008
DOI: 10.1007/s00268-008-9796-1
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Peptic Ulcer: Clinical Presentation, Surgical Outcomes, and the Accuracy of the Boey Scoring System in Predicting Postoperative Morbidity and Mortality

Abstract: Perforated peptic ulcer is associated with high rates of mortality and morbidity. The Boey risk score serves as a simple and precise predictor for postoperative mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
114
7
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 28 publications
(47 reference statements)
14
114
7
5
Order By: Relevance
“…Consistent with the literature, we found that a large perforation diameter significantly increases morbidity and mortality (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Duration of postoperative hospital stay of patients operated for PUP ranges between 7 and 12.5 days (37)(38)(39).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Consistent with the literature, we found that a large perforation diameter significantly increases morbidity and mortality (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Duration of postoperative hospital stay of patients operated for PUP ranges between 7 and 12.5 days (37)(38)(39).…”
supporting
confidence: 75%
“…Turk J Surg 2017; 33: 267-273 There are many scoring systems for predicting risk of morbidity and mortality in PUP, with ASA and Boey scoring methods being the most commonly used ones (29)(30)(31)(32). However, ASA score is used as an overall surgical risk score rather than just for predicting the risks of PUP.…”
mentioning
confidence: 99%
“…Boey's score, which is a score based on factors such as shock on admission, confounding medical illness, and duration of perforation, has been found to be a useful tool in predicting the outcome. [8] In our opinion the Boey's score is a useful prognostic indicator, only at the fi rst contact center because if used at the tertiary center it would be erroneous as it would not take the preoperative resuscitative treatment into account.…”
Section: Discussionmentioning
confidence: 99%
“…Three clinical phases have been identified in the process of PPU [22] . The most simple of the scoring system is Boey scoring system [1,2] which helps in risk stratification post operatively and the parameters includes, • Delay in presentation (>24 hours)…”
Section: Discussionmentioning
confidence: 99%